Carrying Capacity Analysis for Sustainable Coastal Tourism in North Galesong, Takalar Regency - Tang, Beddu; Asmidar, Asmidar; Chuzaimah, Chuzaimah; Darmawati, Darmawati; Tajuddin, Mustamin (Faculty of Fisheries and Marine Science, Brawijaya University, 2026)
North Galesong Sub-district, Takalar Regency, South Sulawesi, Indonesia, has considerable coastal tourism potential that requires sustainable management to prevent environmental degradation. This study aimed to evaluate the carrying capacity of the Galesong Beach tourism area as a basis for sustainable tourism management. Field surveys were conducted at Galesong Beach in Sampulungan Village, using primary data collected through observations, environmental measurements, interviews, and visitor questionnaires. The data included tourism area size, visitor characteristics, environmental conditions, management capacity, and visitor length of stay. The carrying capacity of a tourist area is estimated using the Physical Carrying Capacity (PCC), Real Carrying Capacity (RCC), Management Capacity (MC), and Effective Carrying Capacity (ECC) equations. The tourism area covered 1.8 ha, with 15,200 m² available for tourism activities. The PCC was estimated at 170 visitors per day, exceeding the average visitation of 50 visitors per day. After considering environmental constraints, the RCC decreased to 42 visitors per day, while the MC reached 96.36%, resulting in an ECC of 40 visitors per day or approximately 1,200 visitors per month. These findings provide a scientific basis for regulating visitor numbers and supporting sustainable coastal tourism management in North Galesong.